Higher rates of upgrading and upstaging in older patients undergoing radical prostatectomy and qualifying for active surveillance. (22nd January 2014) - Busch, Jonas; Magheli, Ahmed; Leva, Natalia; Ferrari, Michelle; Kramer, Juergen; Klopf, Christian; Kempkensteffen, Carsten; Miller, Kurt; Brooks, James D.; Gonzalgo, Mark L.
<x xml:space="preserve">Abstract</x> Objective To determine pathological and oncological outcomes of patients diagnosed with low‐risk prostate cancer in two age cohorts who underwent radical prostatectomy (RP) and qualified for active surveillance (AS) according to Prostate Cancer Research International: Active Surveillance (PRIAS) criteria, as AS for low‐risk prostate cancer represents an acceptable management strategy especially for older patients. Patients and Methods In all, 320 patients aged ≥65 years who underwent RP and were eligible for AS according to PRIAS criteria were propensity score matched 1:1 to patients aged <65 years. Patient characteristics were compared with chi‐square, Kruskal–Wallis, and one‐way anova tests. Predictors of RP pathological upgrading or upstaging were analysed using logistic regression. Recurrence‐free survival (RFS) and overall survival (OS) were calculated using the Kaplan–Meier method. Predictors of RFS were analysed within Cox regression models. Results Pathological upgrading and upstaging were significantly higher among older (≥65 years) vs younger (<65 years) patients (53.1% vs 44.1% and 12.2% vs 7.2%, respectively). Higher prostate‐specific antigen levels and increasing age were independent predictors of upgrading among patients aged <65 years. There were no differences in RFS or OS between the two age groups. Positive surgical margin status was the only independent predictor of shorter RFS. Conclusions Patients aged ≥65 years who are eligible for AS by PRIAS criteria have a higher risk of being upgraded and upstaged at RP than those aged <65 years. These findings should be taken into consideration when discussing treatment options for patients diagnosed with prostate cancer.